RECOGNIZING MOVEMENT DISORDER EMERGENCIES - A PRACTICAL REVIEW FOR NON-NEUROLOGIST - Hakeem, Haris; Nasir, Memoona; Khan, Muhammad Farhan; Syed, Nabeel Muzaffar; Rajput, Haris Majid; Ahmad, Arsalan; Javed, Muhammad Athar; Bhatti, Danish Ejaz (Journal of Ayub Medical College Abbottabad, 2019)
Neurology still remains one of the most underserved specialties of medicine in Pakistan with roughly one neurologist per million people. Movement disorders (MD) are neurological problems that interfere with patient's motor abilities and diagnosis is typically clinical. In this review, we describe a practical approach to common MD emergencies that may be encountered by a non-neurologist physician, emphasizing on formulating a working diagnosis and their immediate management. Movement disorder emergencies can be classified based on MD phenomenology and we will provide a brief overview of dystonia including acute dystonic reaction, PAID syndrome and dystonic storm; chorea, myoclonus including serotonin syndrome and startle disease; and rigidity including neuroleptic malignant syndrome and malignant hyperthermia. Keywords: Movement Disorders; Emergency; Neurology; Dystonia; Tardive; Serotonin Syndrome; Neuroleptic Malignant Syndrome